Automatic identification of acute arthritis from ayurvedic wrist pulses. (27th November 2019) - Arunkumar, N.; Shakeel, P. Mohamed; Venkatraman, V.
Traditional ayurvedic doctors examine the state of the body by analysing the wrist pulse from the patient. Mysteriously, the characteristics of the pulses vary corresponding to the various changes in the body. The three pulses acquired from the wrist are named as vata, pitta and kapha. Ayurveda says that when there is imbalance in these three doshas, one will have disease. Two different diseases will have different patterns in their pulse characteristics. Thus, the wrist pulse signal serves as a tool to analyse the health status of a patient. In the earlier work, we have standardised the signals for normal persons and then classified the diabetic cases using approximate entropy (ApEn) (Arunkumar and Sirajudeen, 2011) and later enhanced the results using sample entropy. In the present work, sample entropy (SampEn) is being used to classify for the acute arthritis cases.